The Harvard Medical School Pathways Curriculum: Reimagining Developmentally Appropriate Medical Education for Contemporary Learners. (November 2020) - Schwartzstein, Richard M.; Dienstag, Jules L.; King, Randall W.; Chang, Bernard S.; Flanagan, John G.; Besche, Henrike C.; Hoenig, Melanie P.; Miloslavsky, Eli M.; Atkins, K. Meredith; Puig, Alberto; Cockrill, Barbara A.; Wittels, Kathleen A.; et al.
Abstract : As the U.S. health care system changes and technology alters how doctors work and learn, medical schools and their faculty are compelled to modify their curricula and teaching methods. In this article, educational leaders and key faculty describe how the Pathways curriculum was conceived, designed, and implemented at Harvard Medical School. Faculty were committed to the principle that educators should focus on how students learn and their ability to apply what they learn in the evaluation and care of patients. Using the best evidence from the cognitive sciences about adult learning, they made major changes in the pedagogical approach employed in the classroom and clinic. The curriculum was built upon 4 foundational principles: to enhance critical thinking and provide developmentally appropriate content; to ensure both horizontal integration between courses and vertical integration between phases of the curriculum; to engage learners, foster curiosity, and reinforce the importance of student ownership and responsibility for their learning; and to support students' transformation to a professional dedicated to the care of their patients and to their obligations for lifelong, self-directed learning. The practice of medicine is rapidly evolving and will undoubtedly change in multiple ways over the career of a physician. By emphasizing personal responsibility, professionalism, and thinking skills over content transfer, the authors believe this curriculum will prepare students not only for the first day of practice but also for an uncertain future in the biological sciences, health and disease, and the nation's health care system, which they will encounter in the decades to come. Abstract : Supplemental Digital Content is available in the text.